Glucosinolates and myrosinase activity in moringa oleifera - Asheladevi Ahmad (2019)
Studies were carried out on analysis of glucosinolates, a class of phytochemicals of Moringa oleifera spesies by reverse-phase high performance liquid chromatography (RP-HPLC). Intact glucosinolates from Moringa oleifera leaves, flowers, pods and root were extracted with hot methanol-water (70:30) mixture to inactivate the endogenous myrosinase. The levels of intact glucosinolates in various part of Moringa oleifera was calculated from a standard curve of freshly prepared pure sinigrin (allyl-glucosinolate). Among all the plant parts analyzed, pods contain the highest levels of glucosinolates followed by flowers, leaves and roots. The effect of extrinsic factors (temperature and pH) and intrinsic factors (ascorbic acid and Fe2+) on myrosinase activity was evaluated in order to study the glucosinolatesmyrosinase system in Moringa oleifera plant. The most favorable temperature for myrosinase activity in all plant parts was 35⁰C and the activity decreased as the temperature increased. While, the optimal pH for myrosinase activity in leaves, flowers and pods was at pH7 except for root, a broad pH ranging from 3.0- 9.0 was observed. Myrosinase activities in Moringa oleifera plant were activated by ascorbic acid and ferrous ions at concentration as low as 2 mM. The activities in different plant part were varied, but all parts indicate some myrosinase activity.